Does the Underlying Cause of Arthritis Affect the Outcome of Total Ankle Replacement? A 10 Year Follow Up Study - Andrea Pujol Nicolas FRCS; Anna Porter; Jayasree R. Ramaskandhan BPT, MPT, MSc, PhD; Samir Hakeem FRCS; Nicole Abdul MBChB, BMedSci, MClinRes, MRCS; Mohammad Alkhreisat MD, FRCS; Simon Chambers FRCS; Sultan Qasim; Paulo Torres; Malik Siddique FRCS (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: Total ankle replacement (TAR) is gaining popularity as a treatment option for end stage arthritis. We analysed whether the underlying pathology leading to the arthritis has any bearing on patient reported or clinical outcomes. Methods: Patient-reported outcome measures (PROMs) for TAR performed from 2006 to 2010 by a single surgeon were reviewed. This included WOMAC score, SF-36 and patient satisfaction scores. Data was collected preoperatively and post- operatively at 1, 2, 5 and 10 year. The indications for TAR were obtained by review of clinical notes and radiographs and these included osteoarthritis (OA), inflammatory arthritis (IA), pilon fracture (PF), ankle fracture (AF), and post-traumatic arthritis without previous fracture (PTOA).PROMs were available for 156 TARs: 81 (51.9%, mean age 65.29) for OA, 28 (17.9%, mean age 65.29) for AF, 23 (14.7%, mean age 64.28) for IA, 11 (7%, mean age 55.01) for PF, and 13 (8.3%, mean age 51.08) for PTOA. Results: At 1 year WOMAC score showed significant worsening pain and stiffness on PTOA group (p=0.023, p=0.001) and worse general health and vitality for the IA group (p=0.0025, p=0.005). At 5 years The PTOA group showed significant worsening stiffness (p=0.048), social and emotional domains (p=0.004, P=0.029) and worsening pain, return recreational activities and surgery dissatisfaction (p < 0.05, p=0.032, p=0.023). At 10 years 50% of IA patients were unhappy with return to ADLs but no other difference were found between groups. There was a higher revision rate at 10 years in the PTOA group with 30.7% of patients being revised (4/13) compared to other groups (OA-6.17%, AF-3.57%, IA-4.35%, PF-9%) Conclusion: Similar outcomes in all groups were seen at 10 years but higher revision rates were present in PTOA group. In patients with PTOA careful consideration and counselling is needed prior to proceed with TAR.